Prediagnosis Insights Into Amyotrophic Lateral Sclerosis: Clinical Symptoms and Medication Use - Chunyang Pang; Wen Cao; Jiali Xie; Yaojia Li; Luyi Zhu; Huan Yu; Dongsheng Fan; Binbin Deng (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Amyotrophic lateral sclerosis (ALS) has a prolonged latency period, though its preclinical characteristics remain poorly understood. This study uses UK Biobank data to explore and compare ALS's pre‐diagnostic features, including symptoms and medication use, aiming to provide insights into the disease's underlying mechanisms. Methods Clinical symptoms and medications were identified from self‐reports, hospital records, and death registry data. Propensity score matching was used to match ALS with Alzheimer's disease (AD) and Parkinson's disease (PD), ensuring balance in socioeconomic factors to compare symptoms 0–5 years before diagnosis. Cox regression analysis was applied to assess the associations between medication use and the risk of incident ALS and mortality after ALS diagnosis. Results A total of 753 ALS cases were observed in 502 417 participants, with an incidence rate of 10.58 per 100 000 person‐years. In the ALS cohort, the male‐to‐female ratio was 2.9, with a median age at onset of 64.61 years (Interquartile range (IQR): 56.80–71.31) and a median survival time post‐diagnosis of 9.08 months (IQR: 3.18–18.98), while females (log‐rank p = 0.038) and individuals with earlier (< 64.61 years) disease onset (log‐rank p < 0.001) had longer survival periods. In the 5 years prior to diagnosis, ALS showed a higher incidence of falls compared to ad (11.3% vs. 3.2%, p < 0.001), but a lower incidence than PD (10.7% vs. 28.3%, p < 0.001). Additionally, ALS had a lower incidence of depression (4.6% vs. 25.6%, p < 0.001), anxiety (3.5% vs. 18.1%, p < 0.001), sleep disorders (1.4% vs. 7.2%, p < 0.001), hypotension (3.4% vs. 30.5%, p < 0.001), constipation (0.3% vs. 4.9%, p < 0.001), and urinary dysfunction (2.2% vs. 8.7%, p < 0.001) compared with PD. The use of calcium channel blockers may be a risk factor for incident ALS (adjusted HR 1.61, 95% CI: 1.22–2.12, p < 0.001). Conclusions Pre‐diagnostic presentations of falls are more frequent in ALS than in AD, but less frequent than in PD. However, ALS exhibits fewer psychiatric symptoms and autonomic dysfunction compared with PD. The use of calcium channel blockers may be associated with an increased risk of developing ALS in the future.